PERTUMBUHAN PENJUALAN, JAMINAN ASET, UKURAN PERUSAHAAN, RETURN ON EQUITY, CURRENT RATIO, DAN EARNINGS PER SHARE TERHADAP KEBIJAKAN DIVIDEN PADA SEKTOR OTOMOTIF - ELIYANTI ELIYANTI; STELLA STELLA (Media Bisnis, 2019)
The purpose of this study was to determine the effect of Sales Growth, Collateral Asset, Firm size, Return on Equity, Current Ratio and Earnings per Share on the Dividend Policy on automotive sector in Indonesia Stock Exchange. Population of this research are automotive companies listed in Indonesia Stock Exchange from 2012-2015. The samples of this study are 8 companies using purposive sampling method. This research uses multiple regression method for data analysis. The result of this study shows that Collateral Asset have influence to dividend policy. Sales Growth, Firm Size, Return on Equity, and Earnings per Share do not have influence to capital structure.